Physical and mechanical properties of thermally modified wood from E. grandis - Calonego, Fred Willians [UNESP]; Severo, Elias Taylor Durgante [UNESP]; Ballarin, Adriano Wagner [UNESP] (Springer, 2012)
This study was aimed at evaluating the effect of thermal treatment on the physical and mechanical properties of Eucalyptus grandis wood. Boards were taken from 5.9-year-old E. grandis trees. The boards were thermally modified at temperatures up to 220A degrees C in the Laboratory of Wood Drying and Preservation from UNESP, Botucatu, SP, in Brazil. The results indicated that the thermal modification caused significant decreases of up to: (1) 49.3% and 10.5% in the equilibrium moisture content and in the density of wood, respectively; (2) 53.3% in the volumetric swelling; (3) 52.3% in the modulus of rupture at static bending, without changes in the compressive strength parallel to grain and the respective modulus of elasticity; and (4) 20.7% in the Janka hardness. It was found that the specific gravity and compression parallel to the grain test were not the most suitable ones for evaluating the quality of thermally modified wood.